SunSmart Accreditation and Use of a Professional Policy Drafting Service: Both Positively and Independently Associated with High Sun Protective Hat Scores Derived from Primary School Policies - Petersen, A.-C. L.; McNoe, B.; Iosua, E. E.; Reeder, A. I. (Journal of skin cancer, 2020)
Background. The head and neck are exposed to the highest solar ultraviolet radiation levels and experience a disproportionate skin cancer burden. Sun protective hats can provide an effective barrier. Since early life exposure contributes to skin cancer risk, the World Health Organisation recommends prevention programmes in schools. The New Zealand SunSmart Schools programme is one example. Two criteria concern wearing hat outdoors: students are required to wear a hat providing protection for the face, neck, and ears; if a suitable hat is not worn, students must play in shaded areas. Objectives. To investigate two internationally relevant interventions as plausible statistical predictors of hat policy strength: (1) skin cancer primary prevention programme membership, (2) use of a professional policy drafting service. Methods. Of 1,242 (62%) eligible schools participating in a 2017 national survey, 1,137 reported a sun protection policy and 842 were available for categorising and allocating protective scores (0–3). Results. In multinomial (polytomous) logistic regression models of cross-sectional association, adjusted for school characteristics, SunSmart accredited schools and those utilising a policy drafting service were independently significantly more likely than their counterparts to obtain the most protective compared to the least protective hat score (respectively, RRR 6.48: 95% CI 3.66, 11.47; 7.47: 3.67, and 15.20). For the dichotomous shade measure, similar associations were found using adjusted logistic regression (OR 3.28: 95% CI 2.11, 5.09; 2.70: 1.54, 4.74). Conclusions. Our findings provide support for two plausible interventions that could potentially be implemented beneficially in primary schools via established infrastructure in any jurisdiction, internationally.